2015
DOI: 10.1088/0957-4484/26/7/075401
|View full text |Cite
|
Sign up to set email alerts
|

Light absorption processes and optimization of ZnO/CdTe core–shell nanowire arrays for nanostructured solar cells

Abstract: The absorption processes of extremely thin absorber solar cells based on ZnO/CdTe core-shell nanowire (NW) arrays with square, hexagonal or triangular arrangements are investigated through systematic computations of the ideal short-circuit current density using three-dimensional rigorous coupled wave analysis. The geometrical dimensions are optimized for optically designing these solar cells: the optimal NW diameter, height and array period are of 200 ± 10 nm, 1-3 μm and 350-400 nm for the square arrangement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The possibility to form ZnO NWs using various deposition techniques, including low‐cost and low‐temperature chemical bath deposition (CBD), and to take advantage of their unique properties has thus raised more interest. Within the core–shell NW heterostructure configuration, and following the type‐II band alignment, ZnO NW‐based heterojunction devices offer efficient light‐trapping processes through optically guided and radiated modes, efficient charge carrier separation over the small radius of the NWs, and efficient charge carrier collection owing to the high mobility electron pathways provided by the NWs . ZnO NW‐based core–shell heterostructures have successfully been integrated into gas sensors, UV photodetectors, as well as dye‐sensitized and extremely thin absorber solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to form ZnO NWs using various deposition techniques, including low‐cost and low‐temperature chemical bath deposition (CBD), and to take advantage of their unique properties has thus raised more interest. Within the core–shell NW heterostructure configuration, and following the type‐II band alignment, ZnO NW‐based heterojunction devices offer efficient light‐trapping processes through optically guided and radiated modes, efficient charge carrier separation over the small radius of the NWs, and efficient charge carrier collection owing to the high mobility electron pathways provided by the NWs . ZnO NW‐based core–shell heterostructures have successfully been integrated into gas sensors, UV photodetectors, as well as dye‐sensitized and extremely thin absorber solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…Such a finding can restrict substantially the parametric space of the considered LED coloring designs and simplify significantly the subsequent optimizations. Most importantly, if one is able to find, without computationally heavy schemes [31,41], a set with several candidate designs exhibiting ultra-high performance, one can perform a secondary sweep within this set by posing extra constraints or demands (cost, ease of fabrication, durability, etc. ).…”
Section: B Strategy and Optimizationmentioning
confidence: 99%
“…Michallon et al. , rigorously investigated the optical behavior of extremely thin absorber solar cells based on ZnO/CdTe core–shell nanowire (NW) arrays with square, hexagonal, or triangular arrangements, using three‐dimensional rigorous coupled wave analysis (RCWA). It was concluded that the light absorption is more efficient in the NW square arrangement than in the hexagonal and triangular arrangements .…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports available on the optical modeling and simulation of different geometrical shapes, sizes, and materials. [42][43][44][45][46][47][48][49][50][51]. Few years ago, optical properties of c-Si nanohole array structures for solar photovoltaic applications were investigated [42] and it was found that the nanohole absorption is better than nanorod arrays for solar cells application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation